Taboo Words in Devayan, a Language in Simeulu Island, Aceh Indonesia - Muhammad Wiwin; Zulfadli A. Aziz (English Education Journal, 2019)
The research on taboo words in Devayan has not been conducted yet, and thus, this study investigated the taboo words in Devayan society. This research was a descriptive qualitative study. The technique used was in-depth interview by digging much information from informants about taboo words in the language. The data in this study were analyzed by using Miles and Huberman’s framework (1984), namely data reduction, data display, and conclusion: drawing/verification. The results of this study were (1) taboo words related to sex, (2) taboo words related to the natural function of the human body, (3) taboo words related to the sexual activity, (4) taboo words related to misconduct, (5) taboo words related to deficiency, and (6) taboo words related to animals.